Clinical, dermoscopic, and histopathologic findings of hidroacanthoma simplex: a case report and literature review (Dermatology Reports, 2022)
Hidroacanthoma simplex (HS) is a rare benign intraepidermal tumor that originates in the acrosyringial portion of the eccrine duct. Clinically, they are well-defined lesions, flat or verrucous brownish plaque, and can be misdiagnosed with other types of benign or malignant tumors. Dermoscopy reveals small black globules and fine scales. The histopathology of HS is characterized by typical intraepidermal nests, well-circumscribed, composed of uniform basaloid and poroid cells within the acanthotic epidermis with cystic or ductal structures in the nests. We report a case of HS that changes its clinical appearance, dermoscopy, and histopathologic findings over time. Differential diagnoses included seborrheic keratosis, Bowen disease, melanoma, and malignant HS.